Ferric carboxymaltose in patients with pulmonary arterial hypertension and iron deficiency: a long‐term study. Issue 6 (9th September 2021) - Kramer, Tilmann; Wissmüller, Max; Natsina, Kristiana; Gerhardt, Felix; ten Freyhaus, Henrik; Dumitrescu, Daniel; Viethen, Thomas; Hellmich, Martin; Baldus, Stephan; Rosenkranz, Stephan
Abstract: Background: Pulmonary arterial hypertension (PAH) is a progressive disease with limited survival. Iron deficiency (ID) correlates with disease severity and mortality. While oral iron supplementation was shown to be insufficient in such patients, the potential impact of parenteral iron on clinical measures warrants further investigation. Methods: We retrospectively analysed the long‐term effects of intravenous ferric carboxymaltose (FCM) on iron status and clinical measures in patients with PAH and ID [ferritin < 100 μg/L or ferritin 100–300 μg/L and transferrin saturation (TSAT) < 20%] who were on stable targeted PAH therapy, compared with matched controls without ID. Patients with ID received a single infusion of FCM (500 to 1000 mg). Clinical measures monitored included exercise capacity, World Health Organization (WHO) functional class, ESC/ERS risk status, and hospitalizations. The observation period was up to 18 months. Results: One hundred and seventeen patients (mean age 60.9 ± 16.1 years; 64.1% females) with confirmed PAH and on stable targeted therapy for ≥3 months were included (58 with and 59 patients without ID who did not receive FCM). In patients with ID, iron supplementation with FCM resulted in an immediate and sustained improvement of iron status for up to 18 months (serum iron, ferritin, TSAT, all P < 0.01). Fourteen patients in the FCM group received a second FCM infusion after 9.6 ± 4.8 months due to recurrent ID. At 6 and 18 months after FCM infusion, 6 min walk distance improved from 377.5 ± 15.9 at baseline to 412.5 ± 15.1 and 400.8 ± 14.5 m, respectively (both P < 0.05). WHO functional class ( P < 0.05) and ESC/ERS risk status also improved, and there was a reduction of hospitalizations for worsening PAH in the 12 months post vs. prior to iron repletion ( P = 0.029). No significant changes were observed in the control group. FCM was well tolerated in all patients, with no severe adverse events. Conclusions: In addition to targeted therapy, correction of ID by parenteral iron supplementation with FCM appears feasible and safe, has sustained effects on iron status, and may improve the clinical status and hospitalization rates in patients with PAH. Larger controlled studies are required to confirm this finding.